An investigation of tinnitus using behavioural and functional imaging measures - Davies, Jeff (2016)
Tinnitus is the phantom perception of sound. For some people tinnitus can have a detrimental impact on their quality of life. Negative emotional feelings associated with tinnitus play a major role in enhancing and maintaining its continued presence. Despite its high prevalence across the world, its neurophysiological underpinnings remain elusive and there is no universal cure.